The Effect of Service Quality and Education Cost on Parent Loyalty Through Parent Satisfaction at Pelita Kasih Christian School Lawang - Sabathelia, Sabathelia; Pradiani, Theresia; Rahman, Agus (Universitas Negeri Malang, 2022)
A private educational institution needs to strive for its parental loyalty so it will be the main choice of people who need educational services for their children. Service quality and education costs are thought to be the important factors that shape parental satisfaction and loyalty, so this study aims to examine and analyze whether service quality and education costs affect parental satisfaction and loyalty. A total of 68 parents of elementary students in grades III to VI and junior high students in grades VII to IX from a population of 209 parents of Pelita Kasih Lawang Christian School became respondents using the purposive sampling technique. The research data were then analyzed using Partial Least Square (PLS) technique with SmartPLS 3.3.9 software. The results of the analysis show that service quality has a positive and significant effect on parental satisfaction, but has no effect on parental loyalty, while the cost of education has a positive and significant effect on parental satisfaction, but has no effect on parental loyalty. And, parental satisfaction fully mediates both the quality of service and the cost of education on parental loyalty.